Cable shielding performance testing device - HE CHUNYUAN; BIAN XIAOGANG; XU DEYING; MEI JING; WANG XI; ZHANG RONGPENG (2025)
The utility model relates to the technical field of cable testing, and discloses a cable shielding performance testing device which comprises a testboard and further comprises a moving mechanism which is arranged at the top of the testboard and used for adjusting the distance between installation supports, the moving mechanism comprises a motor, the output end of the motor is fixedly connected with a two-way screw, and the output end of the two-way screw is fixedly connected with a nut. The outer side of the two-way screw is in threaded connection with a support body, the inner wall of the support body is in sliding connection with a sliding rod, the outer sides of the sliding rod and the support body are fixedly connected with limiting plates, and the two ends of the two-way screw are rotationally connected with a first supporting plate and a second supporting plate correspondingly; one side of the first supporting plate is fixedly connected with one side of the motor, and the problems that when two mounting